2014
DOI: 10.4070/kcj.2014.44.2.122
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Sudden Cardiac Death due to Pilsicainide-Induced Torsades de Pointes

Abstract: An 84-year-old male received oral pilsicainide, a pure sodium channel blocker with slow recovery kinetics, to convert his paroxysmal atrial fibrillation to a sinus rhythm; the patient developed sudden cardiac death two days later. The Holter electrocardiogram, which was worn by chance, revealed torsade de pointes with gradually prolonged QT intervals. This drug is rapidly absorbed from the gastrointestinal tract, and most of it is excreted from the kidney. Although the patient's renal function was not highly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Pilsicainide induces tachyarrhythmias such as ventricular tachycardia, as a result of QTc and QRS prolongation (Horita et al, 2004;Kaneko et al, 2012), and bradyarrhythmias such as sinus pause and atrioventricular block (Toeda et al, 2000). As cases of sudden cardiac death have been reported for this drug Frontiers in Pharmacology frontiersin.org (Nakatani et al, 2014), the pro-arrhythmic effects of pilsicainide were speculated to have contributed to this death. The stomach contents showing high concentrations of pilsicainide, furosemide, and verapamil indicated that the patient had ingested pilsicainide along with other drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilsicainide induces tachyarrhythmias such as ventricular tachycardia, as a result of QTc and QRS prolongation (Horita et al, 2004;Kaneko et al, 2012), and bradyarrhythmias such as sinus pause and atrioventricular block (Toeda et al, 2000). As cases of sudden cardiac death have been reported for this drug Frontiers in Pharmacology frontiersin.org (Nakatani et al, 2014), the pro-arrhythmic effects of pilsicainide were speculated to have contributed to this death. The stomach contents showing high concentrations of pilsicainide, furosemide, and verapamil indicated that the patient had ingested pilsicainide along with other drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Pilsicainide induces tachyarrhythmias such as ventricular tachycardia, as a result of QTc and QRS prolongation ( Horita et al, 2004 ; Kaneko et al, 2012 ), and bradyarrhythmias such as sinus pause and atrioventricular block ( Toeda et al, 2000 ). As cases of sudden cardiac death have been reported for this drug ( Nakatani et al, 2014 ), the pro-arrhythmic effects of pilsicainide were speculated to have contributed to this death.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that pilsicainide intoxication induces arrhythmias such as ventricular fibrillation ( 6 ), ventricular tachycardia ( 7 - 9 ), sinus arrest ( 10 ) and atrioventricular block ( 11 ). Conversely, reports of psychiatric symptoms are rare.…”
Section: Discussionmentioning
confidence: 99%
“…These results thus mechanistically explain the good performance of class Ic anti-arrhythmics in terminating atrial fibrillation, but at the cost of increased susceptibility to ventricular arrhythmias. This is for example the case of pilsicainide, a class Ic agent with slow recovery kinetics, successful in the clinical management of atrial fibrillation (Kanki et al, 1998 ; Fukuda et al, 2011 ) in spite of reports of its involvement in precipitating ventricular Torsade de Pointes (TdP) arrhythmias and sudden cardiac death (Nakatani et al, 2014 ), as further corroborated by its “possible risk” TdP category in the CredibleMeds database (Woosley and Romer, 1999 ). These results also hold for the controversial role of flecainide, another class Ic agent especially successful in the treatment of atrial fibrillation (Wang et al, 1992 ; Aliot et al, 2011 ), but with “known risk” TdP category (Woosley and Romer, 1999 ; Nasser et al, 2015 ), although its potent inhibition of potassium repolarizing currents can also mediate its pro-arrhythmic profile (Paul et al, 2002 ; Melgari et al, 2015 ; Passini et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%